2012
DOI: 10.1002/anie.201105629
|View full text |Cite
|
Sign up to set email alerts
|

Toward Wearable Sensors: Fluorescent Attoreactor Mats as Optically Encoded Cross‐Reactive Sensor Arrays

Abstract: Ultrasmall fluorescent sensors and their application for fabrication of wavelength‐addressable virtual sensor arrays capable of sensing metal cations are described. The fluorescent probes generated in situ within the fiber mats can be used as wearable sensors for identifying heavy metal ions in a qualitative and quantitative fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…In contrast to specific targeting, multi-analyte sensing aims to perform discrimination among multiple structure-or propertysimilar analytes, with detectable and differential signal outputs. 95 A key point to the research of sensor arrays is to reduce the sensing molecules and minimize the arrays. 93 The chemical nose consists of sensor arrays, in which a series of responsive and non-specific sensing molecules are invested.…”
Section: Photochromic Sensors For Multi-analyte Discriminationmentioning
confidence: 99%
“…In contrast to specific targeting, multi-analyte sensing aims to perform discrimination among multiple structure-or propertysimilar analytes, with detectable and differential signal outputs. 95 A key point to the research of sensor arrays is to reduce the sensing molecules and minimize the arrays. 93 The chemical nose consists of sensor arrays, in which a series of responsive and non-specific sensing molecules are invested.…”
Section: Photochromic Sensors For Multi-analyte Discriminationmentioning
confidence: 99%
“…g) Wearable NF sensor immersed in a solution of Co 2+ ions and h) consequent fluorescence quenching. Reproduced with permission …”
Section: Optical Sensorsmentioning
confidence: 99%
“…Reproduced with permission. [195] agent. [179] This is attributed to the modification of the protein from its native state to a denaturating one.…”
Section: Fluorescent Optical Sensorsmentioning
confidence: 99%
“…Various sensor arrays for heavy-metal-ion detection using commercial or custom fluorescent indicators have been reported that manifest remarkable selectivity at mM concentrations of the ions. However, extending this performance to the environmentally relevant M concentrations remains a challenge because of the lack of suitable fluorescent indicators [3,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%